2011
DOI: 10.1093/ejo/cjr110
|View full text |Cite
|
Sign up to set email alerts
|

Malocclusions in children at 3 and 7 years of age: a longitudinal study

Abstract: The aim of this longitudinal study was to compare the prevalence of malocclusion at ages 3 and 7 years in a sample of children, exploring the hypothesis that prevalence of malocclusion is higher at 3 than at 7 years of age and may be influenced by sucking habits. The study sample comprised 386 children (199 girls and 187 boys), aged 3 years at study start, sourced from three Public Dental Service clinics in Sweden. Malocclusion was diagnosed by clinical examination, using a specific protocol. Data on allergy, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
92
3
12

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(117 citation statements)
references
References 24 publications
10
92
3
12
Order By: Relevance
“…27 There is some evidence that these habits are associated with dental malocclusion 28 -30 and gingival injury, 31 and that they can also cause local hand infections. 32 -34 Spontaneous correction of some oral malocclusions can occur if thumbsucking habits are stopped before dental development progresses, 35,36 but there is limited research on the long-term effects of these habits on oral health. Our findings suggest that these habits also may have some beneficial effects: although we did not find an impact of these habits on asthma or hay fever, the reduction in atopic sensitization may have long-term health benefits.…”
Section: Discussionmentioning
confidence: 99%
“…27 There is some evidence that these habits are associated with dental malocclusion 28 -30 and gingival injury, 31 and that they can also cause local hand infections. 32 -34 Spontaneous correction of some oral malocclusions can occur if thumbsucking habits are stopped before dental development progresses, 35,36 but there is limited research on the long-term effects of these habits on oral health. Our findings suggest that these habits also may have some beneficial effects: although we did not find an impact of these habits on asthma or hay fever, the reduction in atopic sensitization may have long-term health benefits.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, /s/ and /t/ findings were the most frequent sound error across languages as well. [6][7][8][9][10][11][12][13] In a study by Leavy et al, 16 lingual protrusion was found to be the most common visual inaccuracy among patients with malocclusions. As Subtelny and coworkers 17 noted, the articulatory error of /s/can be a result of excessive fronting of the tongue.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13] Such studies have described a transient effect, with acquired errors resolved within 2 to 3 months. [2][3][4]14 The phonemes acknowledged to present lingering difficulties with articulation are /s/, /f/, /v/, /t/, /r/, /n/, and /l/ phonemes.…”
Section: Introductionmentioning
confidence: 99%
“…Studies assessing the deciduous and mixed dentition stages, when interceptive treatment and developing occlusion guidance measures are typically prescribed, are much less common. Nevertheless, some studies reported that as early as 3 years of age prevalence of malocclusion is as high as 70–82.5% [3,6,7]. Among pre-school children, the most common conditions are anterior open bite (AOB), excessive overjet (OJ), Class II malocclusions, and posterior crossbite (CB) [3,6,8,9].…”
Section: Introductionmentioning
confidence: 99%